2014
DOI: 10.1177/0146621614529646
|View full text |Cite
|
Sign up to set email alerts
|

Person Proficiency Estimates in the Dichotomous Rasch Model When Random Guessing Is Removed From Difficulty Estimates of Multiple Choice Items

Abstract: Andrich, Marais, and Humphry showed formally that Waller's procedure that removes responses to multiple choice (MC) items that are likely to be guessed eliminates the bias in the Rasch model (RM) estimates of difficult items and makes them more difficult. The former did not study any consequences on the person proficiency estimates. This article shows that when the procedure is applied, the more proficient persons who are least likely to guess benefit by a greater amount than the less proficient, who are most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…One procedure to reduce the effects of guessing on parameter recovery in the Rasch model is to code responses as missing when the initial estimate of the item difficulty is considerably higher than the initial estimate of the person ability (Andrich & Marais, 2014; Andrich, Marais, & Humphry, 2012; Choppin, 1983), a procedure labeled tailored calibration. The rationale is that this removes the responses most likely to be affected by guessing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One procedure to reduce the effects of guessing on parameter recovery in the Rasch model is to code responses as missing when the initial estimate of the item difficulty is considerably higher than the initial estimate of the person ability (Andrich & Marais, 2014; Andrich, Marais, & Humphry, 2012; Choppin, 1983), a procedure labeled tailored calibration. The rationale is that this removes the responses most likely to be affected by guessing.…”
mentioning
confidence: 99%
“…When the mean location of the easiest items was set equal across the two models, the negative bias in the other item locations increased with increasing difficulty. The same procedure was followed by Andrich and Marais (2014), who showed that the bias in item parameters produced corresponding bias in person estimates if likely guesses were not recoded as missing. High-ability examinees were penalized because the difficulty of the most difficult items was underestimated.…”
mentioning
confidence: 99%
“…One concern that has been raised regarding the development of multiple-choice tests relates to the plausibility of the distracters (Andrich and Marais, 2014). Poor or implausible distracter options can be easily rejected allowing the participant to choose the correct response by default.…”
Section: Experienced Novicementioning
confidence: 99%
“…As indicated in the introduction, in the studies by Andrich et al. () and Andrich and Marais () the data sets contained responses to MC items only and did not contain any CR items. However, to better assess students’ knowledge and skills, assessments often contain multiple item formats, frequently a combination of MC items and CR items.…”
Section: The Dichotomous Rm and The Control Of Guessingmentioning
confidence: 99%